Phytochemistry, total polyphenol content and antiradical activity of Rauvolfia vomitoria (Apocynaceae) a plant used against asthma in Southern Benin - Agbodjogbé, Kpèdétin Wilfrid Dieu-Donné; AGBODJOGBÉ, Kpèdétin Wilfrid Dieu-Donné; HOUNGBEME, GOUTON ALBAN; MOUSSOUAMI, Simplice Innocent; TCHIKEZO, Mathias; MESSAN, Foly (My University, 2022)
In Benin, as many African countries, people use traditional remedies to treat respiratory diseases. This work aims to contribute to the treatment of asthma by determining the chemical composition and antioxidant efficacy of Rauvolfia vomitoria, a plant species used in primary asthma care in Benin. Phytochemical analysis showed that the leaves contain tannins, terpenes, steroids, mucilages, flavonoids and alkaloids. The quantitative determination of total phenols in the aqueous extract of Rauvolfia vomitoria leaves gives a value of 17.04±0.20 mgEq of gallic acid per g of extract. The decoction of the leaves showed a very marked anti-radical potential with an IC50 = 5.01 ± 0.02 mg/ml but less than that of ascorbic acid (IC50 = 3.97 ± 0.01 mg/ml) used as reference antioxidant.
Keywords: Asthma; R. vomitoria; phytochemical anahysis; antiradical activity; Benin.